Plant and mammalian-derived extracellular vesicles: a new therapeutic approach for the future - Sall, Ibrahima Mamadou; Flaviu, Tabaran Alexandru (Frontiers in Bioengineering and Biotechnology, 2023)
Background: In recent years, extracellular vesicles have been recognized as important mediators of intercellular communication through the transfer of active biomolecules (proteins, lipids, and nucleic acids) across the plant and animal kingdoms, and have considerable roles in several physiological and pathological mechanisms, showing great promise as new therapeutic strategies for a variety of pathologies.Methods: Methods: In this study, we carefully reviewed the numerous articles published over the last few decades on the general knowledge of extracellular vesicles, their application in the therapy of various pathologies, and their prospects as an approach for the future.The recent discovery and characterization of extracellular vesicles (EVs) of diverse origins and biogenesis have altered the current paradigm of intercellular communication, opening up new diagnostic and therapeutic perspectives. Research into these EVs released by plant and mammalian cells has revealed their involvement in a number of physiological and pathological mechanisms, such as embryonic development, immune response, tissue regeneration and cancer. They are also being studied as potential biomarkers for disease diagnosis and as vectors for drug delivery.Conclusions: Nanovesicles represent powerful tools for intercellular communication and the transfer of bioactive molecules. Their molecular composition and functions can vary according to their origin (plant and mammalian), so their formation, composition and biological roles open the way to therapeutic applications in a variety of pathologies, which is arousing growing interest in the scientific community.